Seasonal variation in yield and yield components in gram (Cicer arietinum) - RAMTEKE, S D; CHETTI, M B; SALIMATH, P M (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during rainy and post -rainy seasons of 1992-93 and 1993-94 at Dharwad tostudy the influence of season on yield and yield components of 15 genotypes of gram (Cicer arietinum L.). The numberof flowers were significantly more during rainy season. However, the pod set (%) was less due to less number of podsin rainy than in post-rainy season. Similar trend waspbserved with respect to seed yield also. Among the genotypes, 'K8501' recorded the highest seed yield during rainy season, which also had higher pod dry weight, shelling percentageand harvest index. However, during post-rainy season, the genotypes 'A 1' and 'ICV 2' recorded higher seed yieldcompared with the other genotypes. The genotypes 'Nagpur', 'BG 376', 'BG 374', 'BG 303' and 'NPT' maintainedminimum variation in the yield between rainy and post-rainy seasons.